The Role of Islam in Responsible and Constructive Mass Media - Ainur Awaliah; Lina Pusvivasari (Penerbit Hellow Pustaka, 2025)
The complexity and dynamics of contemporary society's lives are, among other things, complemented by the presence of mass media in the midst of and accompanying their lives. Mass media has been and has always been a part of people's lives, which is used as a good guide as well as a reference for evil. Stopping mass media activities is impossible. However, minimizing the negative effects while maximizing the benefits is a must, to guarantee a better life for the next generation from day to day. Muslim scholars are one element of society that can play a major role in constructing the direction of civilization. The existence and character of mass media must be addressed wisely by Muslim scholars, by optimizing the various strategic roles they can play in order to make mass media a guide for the people towards a good life and future.